1998
DOI: 10.1016/s0301-0082(98)00033-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental strategies to promote axonal regeneration after traumatic central nervous system injury

Abstract: AbstractÐA damage or pathological process that destroys the continuity of axons in the mature central nervous system (CNS) has devastating consequences and produces lasting functional de®cits. One of the major challenges in this ®eld is to stimulate the regrowth of severed axons and reconstruction of pathways. Recent progress in molecular and cell biology has resulted in an explosion of knowledge on factors in the adult CNS being nonsupportive or even actively inhibitory to axonal regrowth. The new ®ndings hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 452 publications
(436 reference statements)
0
60
0
1
Order By: Relevance
“…The antiregenerative properties of the glial scar are predominantly caused by the build-up of various proteoglycans and collagens after injury (Stichel and Muller, 1998;Stichel et al, 1999a, b). Having previously demonstrated that siRNA knock-down of the transcription factor SOX9 down-regulates the expression of CSPG-synthetic enzymes in astrocyte cultures (Gris et al, 2007), we investigated the effect of in vivo Sox9 conditional knock-out on gene expression, glial scarring, and functional recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The antiregenerative properties of the glial scar are predominantly caused by the build-up of various proteoglycans and collagens after injury (Stichel and Muller, 1998;Stichel et al, 1999a, b). Having previously demonstrated that siRNA knock-down of the transcription factor SOX9 down-regulates the expression of CSPG-synthetic enzymes in astrocyte cultures (Gris et al, 2007), we investigated the effect of in vivo Sox9 conditional knock-out on gene expression, glial scarring, and functional recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In both human neurological diseases and animal models of brain injury, cytokines and/or oxidative stress are likely to be involved (107)(108)(109)(110)(111). That cytokines may cause significant brain damage has been clearly demonstrated by results obtained in transgenic mice expressing in astrocytes cytokines such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-3 (IL-3) or interferon-α (IFN-α) under the control of the glial fibrillary acidic protein (GFAP) gene promoter.…”
Section: Transgenic Mice Show That Metallothionein-1and2 Are Essential mentioning
confidence: 99%
“…Cytokines are essential mediators of cell-cell communication in the CNS, with astrocytes, microglia, and brain macrophages as major sources of cytokines as well as a number of growth factors (25,35,38,45,46,54,61,65). In normal conditions, the cellular expression of cytokines in the CNS is very low or absent under tight control.…”
Section: Introductionmentioning
confidence: 99%